Covid-19 telescreening in SUS users with risk conditions: case report - Daniela Arruda Soares; Danielle Souto Medeiros; Clavdia Nicolaevna Kochergin; Matheus Lopes Cortes; Sostenes Mistro; Márcio Galvão Oliveira; José Andrade Louzado; Vanessa Moraes Bezerra; Edson Amaro Jr; Hélio Penna Guimarães; Juliede Rosa da Silva; Maria Tânia Silva Oliveira; et al. (Universidade de São Paulo, 2020)
ABSTRACT This case report aims to describe the conception and preliminary data of the implementation of a telescreening and telemonitoring program of covid-19 for users of the Unified Health System with risk conditions. A system of telerscreening was implemented through which undergraduate students in the health area contact patients by telephone, according to periodicity and predefined criteria, to monitor the evolution of the condition. In eight weeks, 2,190 attempts at remote contact were made with individuals from five health units. The effective number of individuals monitored at the time this writing is 802.